Aid Allocation and Poverty Reduction. - Collier, P; Dollar, D (2002)
This paper derives a poverty-efficient allocation of aid and compares it with actual aid allocations. The allocation of aid that has the maximum effect on poverty depends on the level of poverty and the quality of policies. Using the headcount, poverty-gap, and squared poverty gap measures of poverty, alternatively, all yield similar poverty-efficient allocations. Finally, we find that the actual allocation of aid is radically different from the poverty-efficient allocation. With the present allocation, aid lifts around 10 million people annually out of poverty in our sample of countries. With a poverty-efficient allocation, the productivity of aid would nearly double.